The transmission model of AIDS between mothers and children - Puntani Pongsumpun (My University, 2025)
Human immunodeficiency virus infection (HIV) causes Acquired Immune Deficiency Syndrome(AIDS), which currently has no treatment. The infection can be controlled. The transmission of AIDS can be described by dynamical model. We consider the contact rate between mother and children. We separated the mother and children into susceptible, exposed and infectious population. We analyze the dynamical model. The numerical solutions are presented to confirm our analytical results.
Keywords: HIV/AIDS Impact and Responses; Adolescent Sexual and Reproductive Health; HIV/AIDS Research and Interventions